Modulating the Bioactivity of Mucin Hydrogels with Crosslinking Architecture. (27th January 2021) - Jiang, Kun; Yan, Hongji; Rickert, Carolin; Marczynski, Matthias; Sixtensson, Kajsa; Vilaplana, Francisco; Lieleg, Oliver; Crouzier, Thomas
Abstract: Hydrogels made of crosslinked macromolecules used in regenerative medicine technologies can be designed to affect the fate of surrounding cells and tissues in defined ways. Their function typically depends on the type and number of bioactive moieties such as receptor ligands present in the hydrogel. However, the detail in how such moieties are presented to cells can also be instrumental. In this work, how the crosslinking architecture of a hydrogel can affect its bioactivity is explored. It is shown that bovine submaxillary mucins, a highly glycosylated and immune‐modulating protein, exhibit strikingly different bioactivities whether they are crosslinked through their glycans or their protein domains. Both the susceptibility to enzymatic degradation and macrophage response are affected, while rheological properties and barrier to diffusion are mostly unaffected. The results suggest that crosslinking architecture affects the accessibility of the substrate to proteases and the pattern of sialic acid residues exposed to the macrophages. Thus, modulating the accessibility of binding sites through the choice of the crosslinking strategy appears as a useful parameter to tune the bioactivity of hydrogel‐based systems. Abstract : In this work, it is found that the crosslinking architecture of mucin hydrogels strongly affects the hydrogel bioactive profile. Crosslinking mucins via either protein or glycan domains does not affect rheological properties and barrier to diffusion but affects the accessibility of the substrate to proteases and the pattern of sialic acid residues exposed to the macrophage, which modulates their activity.